Perceptions of people with leprosy about disease and treatment - Pelizzari, Vanessa Daniele Zambon Valério; Arruda, Guilherme Oliveira de; Marcon, Sônia Silva; Fernandes, Carlos Alexandre Molena (Rev Rene, 2016)
Objective: to understand the perceptions of people with leprosy about disease and treatment.Methods: qualitative study conducted with nine adults in chemotherapy treatment. Data was collected through semi-structured interviews and submitted to content analysis in thematic modality. Results: participants reported a concern, distrust, and resistance to accepting the diagnosis. When diagnosed, they felt shame and fear of suffering prejudice. Living with the disease caused important changes, such as the inability to get out, to exercise or perform leisure activities, but the improvement resulting from treatment reassured them, and the need to care for a dependent care motivated them to do it. Families expressed attention, and care was recognized as important, and the absence of these events meant abandonment and exclusion. Conclusion: people with leprosy have demanded not always identified by health professionals, but they had repercussions in the management of the treatment and welfare of these people.